Specific nutrient combination effects on tax, NF-κB and MMP-9 in human T-cell lymphotropic virus -1 positive malignant T-lymphocytes. Issue 1 (December 2015) - Harakeh, Steve; Azar, Rania; Azhar, Esam; Damanhouri, Ghazi; Assidi, Mourad; Abu-Elmagd, Muhammad; Alqahtani, Mohammed; Kumosani, Taha; Niedzwiecki, Aleksandra; Rath, Mathias; Al-Hejin, Ahmed; Barbour, Elie; et al.
Abstract Background Adult T-cell Leukemia (ATL) is a disease with no known cure. The disease manifests itself as an aggressive proliferation of CD4+ cells with the human T-cell Lymphotropic virus type 1 (HTLV-1). The leukemogenesis of the virus is mainly attributed to the viral oncoprotein. Tax activates the Nuclear Factor kappa B (NF-κB) which stimulates the activity and expression of the matrix metalloproteinase-9 (MMP-9). The objective of this study was to investigate the efficacy of a specific nutrient synergy (SNS) on proliferation, Tax expression, NF-κB levels as well as on MMP-9 activity and expression both at the transcriptional and translational levels in two HTLV-1 positive cell lines, HuT-102 and C91-PL at 48h and 96h of incubation. Cytotoxicity of Epigallocatechin-3-gallate (EGCG) was assayed using CytoTox 96 Non-radioactive and proliferation was measured using Cell Titer96TM Nonradioactive Cell Proliferation kit (MTT- based assay). Enzyme linked immunosorbant assay (ELISA) and electrophoretic mobility shift assay (EMSA) were used to assess the effect of SNS on NF-κ B mobility. Zymography was used to determine the effects of SNS on the activity and secretion of MMP-9. The expression of MMP-9 was done using RT-PCR at the translational level and Immunoblotting at the transcriptional level. Results A significant inhibition of proliferation was seen in both cell lines starting at a concentration of 200μg/ml and in a dose dependent manner. SNS induced a dose dependent decrease in Tax expression, which was paralleled by a down-regulation of the nuclearization of NF-κB. This culminated in the inhibition of the activity of MMP-9 and their expression both at the transcriptional and translational levels. Conclusions The results of this study indicate that a specific nutrient synergy targeted multiple levels pertinent to the progression of ATL. Its activity was mediated through the NF-κ B pathway, and hence has the potential to be integrated in the treatment of this disease as a natural potent anticancer agent.